Utilization of molasses sugar for lactic acid production by lactobacillus delbrueckii subsp delbrueckii mutant Uc-3 in batch fermentation - Dumbrepatil, Arti; Adsul, Mukund G.; Chaudhari, Shivani; Khire, Jayant Malhar; Gokhale, Digambar V. (Applied and Environmental Microbiology, 2008)
Efficient lactic acid production from cane sugar molasses by Lactobacillus delbrueckii mutant Uc-3 in batch fermentation process is demonstrated. Lactic acid fermentation using molasses was not significantly affected by yeast extract concentrations. The final lactic acid concentration increased with increases of molasses sugar concentrations up to 190 g/liter. The maximum lactic acid concentration of 166 g/liter was obtained at a molasses sugar concentration of 190 g/liter with a productivity of 4.15 g/liter/h. Such a high concentration of lactic acid with high productivity from molasses has not been reported previously, and hence mutant Uc-3 could be a potential candidate for economical production of lactic acid from molasses at a commercial scale.